Investigating the corrosive effect of KCl on the low alloyed steel T22 at 400°C - Warvne, Jonathan (My University, 2022)
Substituting fossil-fuels with waste- and biomass during combustion for heat-and power production has proven to be a viable, more environmentally friendly energy source. It does however come with new problems, one being the release of a diverse flue gas containing different chlorine species such as KCl, HCl and PbCl2 which are known to greatly accelerate the corrosion of low-alloyed steels commonly used in the waterwall region of waste-fired boilers. To solve this problem a better understanding of the corrosive mechanisms at play during chlorine-assisted corrosion of low alloyed steels at high temperatures is required. This thesis aims to investigate the corro sive effect of KCl on the low-alloyed steel T22 at 400°C through the use of several analytical techniques such as SEM, EDX and XRD. The results reveal that KCl greatly increases the magnitude of corrosion under these conditions as can be seen by both mass-gain data, SEM images and by the extensive crack formation found on salt affected samples after 168h of exposure. XRD-data confirmed the forma tion of Hematite(Fe2O3) and Magnetite(Fe3O4) on nearly all samples. EDX results indicate that Cl can diffuse through the oxide scale and reach the metal interface where it is proposed to form volatile metal-chlorides according to the chlorine cycle mechanism.
Keywords: High-temperature corrosion; Low-alloyed steel; Chlorine-induced corrosion; KCl; HTC